2011
DOI: 10.1287/moor.1110.0500
|View full text |Cite
|
Sign up to set email alerts
|

Flows and Decompositions of Games: Harmonic and Potential Games

Abstract: In this paper we introduce a novel flow representation for finite games in strategic form. This representation allows us to develop a canonical direct sum decomposition of an arbitrary game into three components, which we refer to as the potential, harmonic and nonstrategic components. We analyze natural classes of games that are induced by this decomposition, and in particular, focus on games with no harmonic component and games with no potential component. We show that the first class corresponds to the well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
219
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(227 citation statements)
references
References 47 publications
2
219
0
Order By: Relevance
“…In opposition to the cross-dependent payoffs we can distinguish games with self-dependent payoffs when the payoff matrices are composed of uniform rows. The corresponding elementary games are defined as g(5) = e (2) ⊗ e (1) , (21) g(6) = e (3) ⊗ e (1) , (22) g(7) = e (4) ⊗ e (1) , (23) and the subset of games with self-dependent payoff can be given as…”
Section: Games With Self-and Cross-dependent Payoffsmentioning
confidence: 99%
See 2 more Smart Citations
“…In opposition to the cross-dependent payoffs we can distinguish games with self-dependent payoffs when the payoff matrices are composed of uniform rows. The corresponding elementary games are defined as g(5) = e (2) ⊗ e (1) , (21) g(6) = e (3) ⊗ e (1) , (22) g(7) = e (4) ⊗ e (1) , (23) and the subset of games with self-dependent payoff can be given as…”
Section: Games With Self-and Cross-dependent Payoffsmentioning
confidence: 99%
“…5 shows another universal critical transition occurring when the pair interaction is defined by the matrix A = f (12) + f (23) + f (13) . In that case the corresponding potential matrix has three equivalent maximal values (V 11 = V 22 = V 33 ) that prescribes the existence of three (equivalent) homogeneous ordered states in the limit Monte Carlo data for the strategy frequencies versus noise on the square lattice when the pair interaction is defined as A = f (12) + f (23) + f (13) . Symbols agree with those used in Fig.…”
Section: Coordination Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategy profiles with maximal U (s) correspond to preferred Nash-equilibria (ground states in the terminology of statistical physics). All matrices that define potential games are linear compositions of cross-dependent, self-dependent, and coordinationtype games [12,[15][16][17]. These game classes represent nonstrategic environmental effects, self-determination, and player-player interactions, respectively.…”
Section: Models and General Featuresmentioning
confidence: 99%
“…The concept of matrix decomposition [12,[15][16][17][18] has revealed that payoff matrices, which define player incomes in two-player games [11,12,19,20], are linear combinations of basis matrices that form four orthogonal subsets and represent different types of interactions: self-dependence, cross-dependence, coordination, and cyclic dominance. These game classes are clearly distinguishable via a few key matrix properties.…”
Section: Introductionmentioning
confidence: 99%